2004
DOI: 10.1007/s00020-002-1202-z
|View full text |Cite
|
Sign up to set email alerts
|

Contractions Satisfying the Absolute Value Property $$ |A|^2 \leq |A^2| $$

Abstract: Let B(H) denote the algebra of operators on a complex Hilbert space H, and let U denote the class of operators A ∈ B(H) which satisfy the absolute value condition |A| 2 ≤ |A 2 |. It is proved that if A ∈ U is a contraction, then either A has a nontrivial invariant subspace or A is a proper contraction and the nonnegative operator D = |A 2 |−|A| 2 is strongly stable. A Putnam-Fuglede type commutativity theorem is proved for contractions A in U , and it is shown that if normal subspaces of A ∈ U are reducing, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Very recently B. P. Duggal and authors [3] extend these results to contractions in QA. In this paper, we extend these results to contractions in QA(k), which generalizes results proved for contractions in QA [2].…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Very recently B. P. Duggal and authors [3] extend these results to contractions in QA. In this paper, we extend these results to contractions in QA(k), which generalizes results proved for contractions in QA [2].…”
supporting
confidence: 70%
“…Recently B. p. Duggal, I. H. Jeon and C. S. Kubrusly [2] showed that if A is a class A contraction, then either A has a nontrivial invariant subspace or A is a proper contraction and the non-negative operator D = |A 2 | − |A| 2 is strongly stable (i.e., the power sequence {D n } converges strongly to 0). Very recently B. P. Duggal and authors [3] extend these results to contractions in QA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was extended in [5] to contractions of class U (if a contraction T in U has no nontrivial invariant subspace, then both T and the nonnegative operator |T 2 | − |T | 2 are proper contractions), and to paranormal contractions in [6]: If a paranormal contraction T has no nontrivial invariant subspace, then T is a proper contraction and so is the nonnegative operator |T 2 | 2 − 2|T | 2 + I. In the present paper we extend this result to contractions of class Q.…”
Section: Introductionmentioning
confidence: 90%